The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nano12081337
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Nanogels: Synthesis and Toxicity Profile for Drug Delivery to Articular Joints

Abstract: One important challenge in treating avascular-degraded cartilage is the development of new drugs for both pain management and joint preservation. Considerable efforts have been invested in developing nanosystems using biomaterials, such as chitosan, a widely used natural polymer exhibiting numerous advantages, i.e., non-toxic, biocompatible and biodegradable. However, even if chitosan is generally recognized as safe, the safety and biocompatibility of such nanomaterials must be addressed because of potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…This approach is based on the previously observed effects, such as the synergistic inhibition of endothelin-1 and bradykinin receptors by two peptides, BQ-123 and R-954, respectively, that can decrease pain and prevent the destruction of cartilage in a surgically induced OA model [ 24 ]. CHI- and HA-based nanogels are of interest to improve OA treatments, notably because they could be used as DDS [ 44 , 45 , 46 , 47 ]. In this study, CHI- and HA-based nanogels were developed as a drug delivery platform for the concomitant intra-articular administration of BQ-123 and R-954 peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is based on the previously observed effects, such as the synergistic inhibition of endothelin-1 and bradykinin receptors by two peptides, BQ-123 and R-954, respectively, that can decrease pain and prevent the destruction of cartilage in a surgically induced OA model [ 24 ]. CHI- and HA-based nanogels are of interest to improve OA treatments, notably because they could be used as DDS [ 44 , 45 , 46 , 47 ]. In this study, CHI- and HA-based nanogels were developed as a drug delivery platform for the concomitant intra-articular administration of BQ-123 and R-954 peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Nanogels (NGs) were obtained using an ionic gelation process based on a previously reported protocol [ 47 ]. Briefly, a chitosan solution (CHI, 2.5 mg/mL) in acetic acid (0.5% ( v / v )) and a second solution of sodium tripolyphosphate (TPP, 1.2 mg/mL) (Alfa Aesar, Ward Hill, MA, USA) and 60 kDa sodium hyaluronate (HA, 0.8 mg/mL) were magnetically stirred overnight until complete dissolution.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of chitosan-based nanogels on chondrocytes, synoviocytes, and osteoblasts in patients with osteoarthritis was studied in [ 92 ]. The authors found that the proliferation of these cells exceeds 80% at any concentration of nanogels ( Figure 5 ), and the integrity of the cell membrane is maintained when exposed to nanogels for 72 h.…”
Section: Gels For the Treatment Of Joint Diseasesmentioning
confidence: 99%
“…Chitosan nanoparticles are formed by the interaction of positively charged chitosan with negatively charged molecules such as DNA, RNA, and drugs, via electrostatic interactions [ 1 , 59 , 84 , 85 , 86 , 87 ]. These nanoparticles can be administered to the body via various routes such as oral, topical, or injection [ 78 , 88 , 89 ].…”
Section: Chitosan-based Nanosystem Of Smart Drug Delivery Systemmentioning
confidence: 99%